Health-related quality-of-life outcomes in patients undergoing total hip and knee arthroplasty at Chris Hani Baragwanath Academic Hospital - Fang, K N (My University, 2021)
Background: Total hip and knee arthroplasty are known for effective surgical interventions for relieving pain and restoring function for patients with end-stage osteoarthritis. Their success can be measured using health-related quality-of-life instruments to rationalise the costs and risks involved with surgery. This study aimed to evaluate the impact of total hip and knee arthroplasty on the quality-of-life of patients with end-stage osteoarthritis using disease-specific and generic health-related quality-of-life (HRQoL) outcome measures. Methods: Patients scheduled for primary total hip arthroplasty or total knee arthroplasty for the indication of osteoarthritis were surveyed using the disease-specific outcome measures, Harris Hip Score (HHS) or American Knee Society Score (AKSS), as well as the generic instrument, Medical Outcomes Study Short Form-36 Health (MOS SF-36) survey. Follow-up surveys were administered to all patients at three months post-surgery. Results: A total of fifty patients were included in the study. Twenty-four patients had total hip arthroplasty, and twenty-six patients had total knee arthroplasty. Pre-operative MOS SF-36 scores show the substantial burden of osteoarthritis on patients’ quality-of-life when compared to the normative MOS SF-36 scores. Patients who had primary THA showed significant improvements in the HHS and all parameters of the MOS SF-36 scores. Similarly, patients who had TKA also expressed significant improvement in the AKSS and the MOS SF-36. Comparison between THA and TKA showed no significant differences in the MOS SF-36 outcome measures, except for the physical function parameter, in which THA was superior. A moderate correlation was expressed between the disease-specific instruments and the physical parameters of the generic MOS-SF-36.Post-operatively, patients with TKA scored higher than the norm in all domains of the MOS SF-36 instrument. The same was observed for patients with THA, except for the social functioning domain, which scored lower than the norm post-operatively. Conclusion: THA and TKA are effective surgical interventions used for patients with end-stage osteoarthritis. The disease-specific HHS and AKSS, as well as the generic MOS SF-36 instruments, are responsive in detecting the changes in the HRQoL outcomes in patients undergoing THA and TKA. Level of Evidence: 4
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Orthopaedic Surgery, 2021